Lie Algebroids in the Loday-Pirashvili Category - Rovi, A. (Symmetry, Integrability and Geometry: Methods and Applications, 2015)
We describe Lie-Rinehart algebras in the tensor category LM of linear maps in the sense of Loday and Pirashvili and construct a functor from Lie-Rinehart algebras in LM to Leibniz algebroids.